(untitled) (KULT_online, 2009)
Corinna Kirschstein’s dissertation Theater Wissenschaft Historiographie. Studien zu den Anfängen theaterwissenschaftlicher Forschung in Leipzig (Theatre Studies Historiography: Studies on the Establishment of Theatre Studies in Leipzig) is the first volume in the series "Leipziger Beiträge zur Theatergeschichtsforschung" ("Leipzig contributions to the study of theatre history") edited by Gerda Baumbach. Kirschstein concentrates on the early phase of German theatre studies in the 1920s, with particular reference to the Leipziger Schule lead by professor of German literature Albert Köster. Kirschstein examines the relation between German literary studies and theatre studies as well as the institutional position of theatre history studies of that period, and shows how much the academic debate was dominated by a bourgeois theatre concept. Unfortunately, she misses the opportunity to develop a critical perspective which could have clarified references to contemporary practices in German theatre studies.